2022
DOI: 10.1155/2022/8750394
|View full text |Cite|
|
Sign up to set email alerts
|

Preparation and Performance Analysis of Bacterial Cellulose-Based Composite Hydrogel Based on Scanning Electron Microscope

Abstract: In order to better prepare and analyze bacterial cellulose-based composite hydrogels, an experimental method based on scanning electron microscopy was proposed. The specific content of the method is to observe the hydrogel through scanning electron microscope, to observe the space between molecules through experiments, and to improve the effect of bacterial cellulose preparation of hydrogel. The experimental results show that the gel preparation effect is best when PEG concentration is not more than observed b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 22 publications
0
3
0
Order By: Relevance
“…The obtained integral intensities were used to calculate the crystallinity degree quantitatively by the Rutland-Wonka method (Shao et al 2022, Rabiej 1991. This method primarily uses the ratio of the crystalline phase area to the total area under the diffraction curve, which includes scattering by the amorphous and crystalline phases.…”
Section: Characterization and Comparison Of Bc On Glucose And Sucrosementioning
confidence: 99%
“…The obtained integral intensities were used to calculate the crystallinity degree quantitatively by the Rutland-Wonka method (Shao et al 2022, Rabiej 1991. This method primarily uses the ratio of the crystalline phase area to the total area under the diffraction curve, which includes scattering by the amorphous and crystalline phases.…”
Section: Characterization and Comparison Of Bc On Glucose And Sucrosementioning
confidence: 99%
“…This article has been retracted by Hindawi following an investigation undertaken by the publisher [1]. This investigation has uncovered evidence of one or more of the following indicators of systematic manipulation of the publication process:…”
mentioning
confidence: 99%
“…This article has been retracted by Hindawi following an investigation undertaken by the publisher [ 1 ]. This investigation has uncovered evidence of one or more of the following indicators of systematic manipulation of the publication process: Discrepancies in scope Discrepancies in the description of the research reported Discrepancies between the availability of data and the research described Inappropriate citations Incoherent, meaningless and/or irrelevant content included in the article Peer-review manipulation …”
mentioning
confidence: 99%